Experiments in Moral and Political Philosophy - Viciana, Hugo; Gaitán, Antonio; Aguiar, Fernando (Routledge Studies in Ethics and Moral Theory, 2024)
applied ethics, behavioral ethics, criminal responsibility ethics, experimental bioethics, experimental jurisprudence, experimental moral philosophy, experimental philosophy, feminist X-Phi, folk moral judgments, intuitions, metaethics, moral methodology, reflective equilibrium, self-driving cars, utilitarianism